(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
Adultery is depicted as a widespread but not always hidden part of adult life. While extramarital affairs are often joked about or normalized in the African community, they have really emotional and social consequences. In Aya de Yopougon, Marguerite Abouet and Clément Oubrerie craft a richly layered narrative that captures the everyday realities of life in 1970s Côte d’Ivoire through the lens of humour, satire, and social realism. Central to the story are the intertwined themes of adultery and complex family relationships, issues that serve not only as personal crises for the characters but also as reflections of a society negotiating the tensions between tradition and change. Through a unique blend of visual storytelling and colloquial dialogue, the authors explore how gender roles, generational expectations, and the pressures of reputation shape domestic life in Yopougon. Literary techniques such as irony, caricature, and polyphonic narration allow Abouet and Oubrerie to humanize their characters while critiquing social norms surrounding fidelity, legitimacy, and family honour. Set against the backdrop of a post-colonial African society experiencing both economic development and moral upheaval, Aya de Yopougon uses the personal to illuminate the political, turning intimate betrayals and family secrets into a broader commentary on cultural transformation.